Primary School Mathematics And Science Teachers' Stages Of Concern About The Implementation Of Lesson Study - Chew , Cheng Meng; Lim , Chap Sam; Osman, Shuki (Penerbit Universiti Sains Malaysia, 2015)
In this study, the Japanese model of Lesson Study was introduced as a teacher professional development programme to nine low-performing primary schools in Malaysia. The objectives of this study were to examine to what extent Lesson Study can improve low-performing primary mathematics and science teachers' stages of concern about the implementation of Lesson Study in their schools and their teaching quality as well as student learning performance. The sample consisted of 97 primary mathematics and science teachers from three types of primary schools: the National School (SK); the National Type Chinese School (SJKC) and the National Type Tamil School (SJKT). Before the implementation of Lesson Study, a workshop was conducted in every school to introduce participating teachers to the concepts of Lesson Study and the research procedure. After the workshop, the participating teachers were asked to complete the Stages of Concern Questionnaire (SoCQ) in order to identify their initial stages of concern about the implementation of Lesson Study in their schools. The SoCQ was developed based on the Concerns-Based Adoption Model (CBAM). It consists of 35 items, categorising teachers' concerns into seven stages: Stage 0 (Awareness); Stage 1 (Informational); Stage 2 (Personal); Stage 3 (Management); Stage 4 (Consequence); Stage 5 (Collaboration) and Stage 6 (Refocusing) (George, Hall & Stiegelbauer, Measuring implementation in schools: The stages of concern questionnaire (2006)). The same SoCQ was also given to the participating teachers after every Lesson Study cycle to determine whether their stages of concern changed before and after the implementation of Lesson Study cycles. In this paper, only the data collected from the first SoCQ given were analysed. The results showed that the profiles of the SK, SJKC and SJKT teachers' initial stages of concern about the implementation of Lesson Study in their schools were quite similar. The SK, SJKC and SJKT teachers' concerns were the highest in Stage 0 and the lowest in Stage 4, indicating that these teachers had a high level of concern about a number of other initiatives, tasks, and activities besides Lesson Study and they had quite a low level of concern about the consequences of implementing Lesson Study for their students, respectively